THE RELATIONSHIP OF COOPERATIVE ROLE TO MILK PRODUCTION AND INCOME OF CORPORATE FARMS IN SEMARANG DISTRICT - Fifin, Fifin; Mukson, Mukson; Gayatri, Siwi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Dairy cooperatives play an important role in improving the welfare of member farmers. Working together increases dairy farming and farmer income. However, farmers' income is low despite rising production due to individual sales. The cooperative is expected to increase income through its role with group strength and efficiency. Cooperatives are utilized to increase income through joint milk production. This study analyzes the role of cooperatives in milk production and income generation of farmers in Semarang. The research was carried out by survey method with questionnaires as a research tool. This research was conducted in 3 cooperatives active in Semarang Regency, Andini Luhur KUD, Nusantara KSU and Mekar KUD. Sampling was carried out through the proportional quita sampling method, with 120 breeders as respondents. Data processing was carried out using path analysis as the analysis method. The average ownership of lactating dairy cows was 2,825 heads/farmer, while milk production per head per day increased to 9.92 liters. Dairy income increased from the previous year and was above minimum wage both in 2022 and 2023, which was Rp2,804,300.53 per month. The results of the path analysis show that the role of cooperatives as marketing guarantors has a major role in increasing income through milk production. Thus, to increase the income of dairy farmers, it is necessary to improve the quality of milk production and the development of cooperatives as marketing guarantors. The implementation is expected to increase the income of dairy farmers so that it has implications for the economy of the national dairy farming sector.